Beyond Technology-Facilitated Abuse: Domestic and Family Violence and Temporary Migration - Vasil, Stefani (The British journal of criminology, 2024)
This paper explores the importance of moving beyond a narrow examination of technology-facilitated abuse (TFA) and domestic and family violence (DFV). Drawing on findings from two studies that capture the experiences of over 300 temporary visa holders in Australia, we detail how technology is one tool used within the context of patterns of control and isolation. We detail the experiences of TFA in our sample and then examine the importance of locating TFA within the broader context of structural inequality. We argue that the position of temporary non-citizens must be the foreground to identify the structural conditions that are sustained by the state and leveraged by perpetrators, rather than the specifics of the tools that are used to enact DFV.